1993
DOI: 10.2172/10132560
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subsurface VOCs using a chemical microsensor array. Final report

Abstract: PREFACECun'cnfly available technology is not adequate to assess environmental contamination at Department of Energy (DOE) sites, take permanent remedial action, and eliminate or minimize the environmental impact of futm'eoperations. Technical resources to address these shortcomings exist within the DOE community and the private sector, but the involvement of the private sector ] in attaining permanent and cost=effective solutions has been limited. L During 1990, on bohalf of DOE's Office of Technology I_velopm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For hydrogen bonding substances, derivatives having hydrogen bond acidity have been derived from 4,4-isopropylidenediphenol (bisphenol A) to detect hydrogen bond bases (Abraham et al 1991). Batterman and Zellers (1993) used a sensor array system to determine aliphatic, aromatic, and halogenated hydrocarbons. These investigators tested a wide range of coatings on the SAW device and found that polydiphenoxyphosphazene, polyisobutylene, diethylene glycol adipate, and polychloropene provided the best results with respect to vapor classification.…”
Section: Electrochemicallymentioning
confidence: 99%
“…For hydrogen bonding substances, derivatives having hydrogen bond acidity have been derived from 4,4-isopropylidenediphenol (bisphenol A) to detect hydrogen bond bases (Abraham et al 1991). Batterman and Zellers (1993) used a sensor array system to determine aliphatic, aromatic, and halogenated hydrocarbons. These investigators tested a wide range of coatings on the SAW device and found that polydiphenoxyphosphazene, polyisobutylene, diethylene glycol adipate, and polychloropene provided the best results with respect to vapor classification.…”
Section: Electrochemicallymentioning
confidence: 99%